Diagnostic Delay in Coeliac Disease: A Survey among Danish Patients - Line Lund Kårhus; Susanne Hansen; Jüri J. Rumessen; Allan Linneberg (Canadian Journal of Gastroenterology and Hepatology)
Background. Coeliac disease affects around 1% of the population, although many cases remain undiagnosed. Underdiagnosis and diagnostic delay in coeliac disease may cause health complications and be a burden for both the patient and society. Casuistic reports indicate that the diagnostic delay may be significant in Danish patients. Aim. To investigate the diagnostic delay among Danish patients with coeliac disease. Methods. We performed a survey among coeliac disease patients to investigate the diagnostic delay. A web-based questionnaire was sent to all members of The Danish Coeliac Society. Results. The questionnaire was completed by 1,392 individuals with a diagnosis of coeliac disease (78.1% women; mean age: 42.8 years). The mean delay was 1.8 (SD 5.0) years from the first symptom to the first health care contact and 5.8 (SD 9.5) years from the first symptom to diagnosis; 18.6% of the participants reported a total diagnostic delay of more than 10 years. Among the patient-reported reasons for delay were misunderstandings, unspecific symptoms, and a lack of knowledge or focus on coeliac disease among the doctors. In total, 52.7% rated the time to diagnosis to have been “too long,” and 20.1% were not satisfied with the diagnostic process. However, the majority were “to some extent” or “very” satisfied with the diagnostic process. Conclusion. We found evidence of a significant diagnostic delay among Danish patients with coeliac disease. This was primarily due to the delay from the time of first health care contact to the time of diagnosis. This study highlights the importance of raising awareness of coeliac disease among health care professionals.